Estudo experimental e numérico de antena ressoadora dielétrica (DRA) baseada em Sr2CoNbO6 - Morais, José Eduardo Vasconcelos de (2014)
The purpose of this work was to study the dielectric properties in Radio Frequency ( RF) and microwave compound Sr 2 CoNbO 6 ( SCNO ) adding with titanium oxide ( TiO 2 ) in percentages ranging from 15 % to 22 % by mass. The SCNO is a double perovskite , which was prepared by the met hod of solid state reaction . The samples were characterized structurally by x - ray diffraction (XRD ). The method used to obtain the desired phase was by Rietveld refinement , showed that formant type cubic symmetry pm3m. The dielectric properties : dielectr ic constant ( ε ' ) and dielectric loss ( tg δ ) were measured at room temperature in the frequency range of 100 KHz to 2GHz , showed that the permittivity decreases with frequency below 50 MHz the dielectric constant is very high and above 1GHz appears low. The picnometry performed showed that the relative densities were all above 9 0 %. For the study of microwave stay full it was applied the method of Hak ki Coleman, which showed growth of the dielectric permittivity with increasing concentration of TiO 2 ( 14 - 52) a nd loss tangent ranging from 10 - 1 - 10 - 4 . The temperature coefficient of resonant frequency ( τ f) showed that SCNO τ f has a negative ( - 634ppm/oC) . With the addition of TiO 2 τ f showed positive results. The numerical simulation of the dielectric res onator antenna ( DRA ) based on SCNO and added with TiO 2 was performed with HFSS ® and the results were q uite consistent with the experiments . The low gain and a small presented to the SCNO efficiency was improved substantially with the addition of TiO 2 . These properties can be improved with a proposal for a new geometry for dielectric res o nator antenna ( D RA ) and with addition of TiO 2 in new percentages for analysis of dielectric properties and parameters of antennas